Analysis Of Entrepreneurial Soft Skills In Improving MSME Business Sustainability In Pasuruan Mangrove Tourism Area - Moh. Faizin; Arif Isnaini; Sudarmiatin Sudarmiatin; Rizky Firmansyah (International Journal of Economics and Management Research, 2024)
The mangrove tourism area in Pasuruan has become an important economic potential through the existence of Micro, Small and Medium Enterprises MSMEs. This phenomenon shows that MSMEs have a strategic role in building the local economy, especially in the tourism sector. MSMEs in the Pasuruan mangrove tourism area may face unique challenges related to entrepreneurial soft skills that can affect their business sustainability. This issue involves local factors such as culture, markets, and local government policies. Ideally, MSMEs in the Pasuruan mangrove tourism area need to understand and develop entrepreneurial soft skills to maintain and improve the sustainability of their business. This research aims to provide deeper insight and understanding regarding the role of entrepreneurial soft skills in supporting MSME business sustainability. Although there are several studies related to entrepreneurship and business sustainability, there is still a research gap, especially in the context of MSMEs in the Pasuruan mangrove tourism area. The novelty of this research lies in its focus on entrepreneurial soft skills in the context of MSME business in the Pasuruan mangrove tourism area, which has not been studied in depth before. The sustainability of MSME business has a positive impact on local economic growth and regional development. Therefore, a better understanding of the role of entrepreneurial soft skills is very urgent to improve the competitiveness and sustainability of MSMEs in the Pasuruan mangrove tourism area. The main objective of this study is to analyze the role of entrepreneurial soft skills in improving MSME business sustainability in the Pasuruan mangrove tourism area, by exploring its positive impact on economic and social aspects. This research use desciptive qualitative approach. The research subjects involved MSMEs. Data collection was carried out through observation, interviews and documentation. Data analysis involves data reduction, display, and inference, with triangulation used to ensure validity.The results of research, observations, and interviews show that in this study, MSME actors in the Pasuruan Mangrove Tourism Area showed creativity, adaptability, and good communication skills. They also have quick collaboration and problem-solving skills. The success of MSME businesses is reflected in their resilience to environmental changes and market dynamics. Close partnerships with local communities also make a positive contribution. Their business strategy involves product diversification, technology utilization, and external cooperation, while maintaining environmental sustainability. Recommendations involve soft skills training and support on product innovation to improve competitiveness and business sustainability.